A systematic review of p53 regulation of oxidative stress in skeletal muscle. (1st January 2018) - Beyfuss, Kaitlyn; Hood, David A.
ABSTRACT: Background: p53 is a tumor suppressor protein involved in regulating a wide array of signaling pathways. The role of p53 in the cell is determined by the type of imposed oxidative stress, its intensity and duration. The last decade of research has unravelled a dual nature in the function of p53 in mediating the oxidative stress burden. However, this is dependent on the specific properties of the applied stress and thus requires further analysis. Methods: A systematic review was performed following an electronic search of Pubmed, Google Scholar, and ScienceDirect databases. Articles published in the English language between January 1, 1990 and March 1, 2017 were identified and isolated based on the analysis of p53 in skeletal muscle in both animal and cell culture models. Results: Literature was categorized according to the modality of imposed oxidative stress including exercise, diet modification, exogenous oxidizing agents, tissue manipulation, irradiation, and hypoxia. With low to moderate levels of oxidative stress, p53 is involved in activating pathways that increase time for cell repair, such as cell cycle arrest and autophagy, to enhance cell survival. However, with greater levels of stress intensity and duration, such as with irradiation, hypoxia, and oxidizing agents, the role of p53 switches to facilitate increased cellular stress levels by initiating DNA fragmentation to induce apoptosis, thereby preventing aberrant cell proliferation. Conclusion: Current evidence confirms that p53 acts as a threshold regulator of cellular homeostasis. Therefore, within each modality, the intensity and duration are parameters of the oxidative stressor that must be analyzed to determine the role p53 plays in regulating signaling pathways to maintain cellular health and function in skeletal muscle. Abbreviations: Acadl: acyl-CoA dehydrogenase, long chain; Acadm: acyl-CoA dehydrogenase, C-4 to C-12 straight chain; AIF: apoptosis-inducing factor; Akt: protein kinase B (PKB); AMPK: AMP-activated protein kinase; ATF-4: activating transcription factor 4; ATM: ATM serine/threonine kinase; Bax: BCL2 associated X, apoptosis regulator; Bcl-2: B cell Leukemia/Lymphoma 2 apoptosis regulator; Bhlhe40: basic helix-loop-helix family member e40; BH3: Borane; Bim: bcl-2 interacting mediator of cell death; Bok: Bcl-2 related ovarian killer; COX-IV: cytochrome c oxidase IV; cGMP: Cyclic guanosine monophosphate; c-myc: proto-oncogene protein; Cpt1b: carnitine palmitoyltransferase 1B; Dr5: death receptor 5; eNOS: endothelial nitric oxide synthase; ERK: extracellular regulated MAP kinase; Fas: Fas Cell surface death receptor; FDXR: Ferredoxin Reductase; FOXO3a: forkhead box O3; Gadd45a: growth arrest and DNA damage-inducible 45 alpha; GLS2: glutaminase 2; GLUT 1 and 4: glucose transporter 1(endothelial) and 4 (skeletal muscle); GSH: Glutathione; Hes1: hes family bHLH transcription factor 1; Hey1: hes related family bHLH transcription factor with YRPW motif 1; HIFI- α : hypoxia-inducible factor 1, α -subunit; HK2: Hexokinase 2; HSP70: Heat Shock Protein 70; H2 O2 : Hydrogen Peroxide; Id2: inhibitor of DNA-binding 2; IGF-1-BP3: Insulin-like growth factor binding protein 3; IL-1 β : Interleukin 1 beta; iNOS: inducible nitric oxide synthase; IRS-1: Insulin receptor substrate 1; JNK: c-Jun N-terminal kinases; LY-83583: 6-anilino-5, 8-quinolinedione; inhibitor of soluble guanylate cyclase and of cGMP production; Mdm 2/ 4: Mouse double minute 2 homolog (mouse) Mdm4 (humans); mtDNA: mitochondrial DNA; MURF1: Muscle RING-finger protein-1; MyoD: Myogenic differentiation 1; MyoG: myogenin; Nanog: Nanog homeobox; NF-kB: Nuclear factor-κB; NO: nitric oxide; NoxA: phorbol-12-myristate-13-acetate-induced protein 1 (Pmaip1); NRF-1: nuclear respiratory factor 1; Nrf2: Nuclear factor erythroid 2-related factor 2; P21: Cdkn1a cyclin-dependent kinase inhibitor 1A (P21); P38 MAPK: mitogen-activated protein kinases; p53R2: p53 inducible ribonucleotide reductase gene; P66Shc: src homology 2 domain-containing transforming protein C1; PERP: p53 apoptosis effector related to PMP-22; PGC-1 α : Peroxisome proliferator-activated receptor gamma coactivator 1-alpha; PGM: phosphoglucomutase; PI3K: Phosphatidylinositol-4, 5-bisphosphate 3-kinase; PKC β : protein kinase c beta; PTEN: phosphatase and tensin homolog; PTIO: 2-phenyl-4, 4, 5, 5, -tetramethylimidazoline-1-oxyl 3-oxide (PTIO) has been used as a nitric oxide (NO) scavenger; Puma: The p53 upregulated modulator of apoptosis; PW1: paternally expressed 3 (Peg3); RNS: Reactive nitrogen species; SIRT1: sirtuin 1; SCO2: cytochrome c oxidase assembly protein; SOD2: superoxide dismutase 2; Tfam: transcription factor A mitochondrial; TIGAR: Trp53 induced glycolysis repulatory phosphatase; TNF-a: tumor necrosis factor a; TRAF2: TNF receptor associated factor 2; TRAIL: type II transmembrane protein.